Development of a core outcome set for traumatic brachial plexus injuries (COMBINE): study protocol. Issue 6 (14th June 2019) - Miller, Caroline; Cross, Jane; Power, Dominic M; Kyte, Derek; Jerosch-Herold, Christina
Abstract : Introduction: Traumatic brachial plexus injury (TBPI) involves major trauma to the large nerves of the arm which control the movement and sensation. Fifty per cent of injuries result in complete paralysis of the arm with many other individuals having little movement, sensation loss and unremitting pain. The injury often causes severe and permanent disability affecting work and social life, with an estimated cost to the National Health Service and the economy of £35 million per annum. Advances in microsurgery have resulted in an increase in interventions aimed at reconstructing these injuries. However, data to guide evidence-based decisions is lacking. Different outcomes are used across studies to assess the effectiveness of treatments. This has impeded our ability to synthesise results to determine which treatments work best. Studies frequently report short-term clinical outcomes but rarely report longer term outcomes and those focused on quality of life. This project aims to produce a core outcome set (COS) for surgical and conservative management of TBPI. The TBPI COS will contain a minimum set of outcomes to be reported and measured in effectiveness studies and collected through routine clinical care. Methods and analysis: This mixed-methods project will be conducted in two phases. In phase 1 a long list of patient-reported and clinical outcomes will be identified through a systematic review. Interviews will then explore outcomes important to patients. In phase 2, the outcomes identified across the systematic review, and the interviews will be included in a three-round online Delphi exercise aiming to reach consensus on the COS. The Delphi process will include patient and healthcare participants. A consensus meeting will be held to achieve the final COS. Ethics and dissemination: The use of a COS in TBPI will increase the relevance of research and clinical care to all stakeholders, facilitate evidence synthesis and evidence-based decision making. The study has ethical approval. Trial registration numbers: CRD42018109843.